2002
DOI: 10.1053/ejvs.2002.1611
|View full text |Cite
|
Sign up to set email alerts
|

The Early Effect of Lipid-lowering Treatment on Carotid and Femoral Intima Media Thickness (IMT)

Abstract: cholesterol-lowering with atorvastatin 20 mg/day leads to a decrease in CCA-IMT and CFA-IMT. This difference achieved significance after 8 weeks of treatment, but a trend was visible at 4 weeks. These rapid changes in IMT may be attributable to an anti-inflammatory effect. IMT measurement may be a useful tool to rapidly assess the effect of drug treatment on the atherosclerotic process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(52 citation statements)
references
References 40 publications
2
48
0
2
Order By: Relevance
“…In studies with statins, which are believed to ameliorate the prognosis and development of atherosclerosis by modifying the underlying inflammatory process, short-term treatments have decreased markers of systemic inflammation [28] and have reduced atherosclerosis [29] as well as improved endothelial function in vitro [30] and in vivo [31,32,33]. Treatment of rheumatoid arthritis with etanercept, at the doses used in this study, provides clinical improvement within 2 weeks [34] as well as a decrease in systemic inflammatory markers [35].…”
Section: Discussionmentioning
confidence: 99%
“…In studies with statins, which are believed to ameliorate the prognosis and development of atherosclerosis by modifying the underlying inflammatory process, short-term treatments have decreased markers of systemic inflammation [28] and have reduced atherosclerosis [29] as well as improved endothelial function in vitro [30] and in vivo [31,32,33]. Treatment of rheumatoid arthritis with etanercept, at the doses used in this study, provides clinical improvement within 2 weeks [34] as well as a decrease in systemic inflammatory markers [35].…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14] There are now several reports on the effects of statins (mainly atorvastatin and simvastatin) on renal function and SUA levels as well as their contribution to CHD risk reduction. 8,9,[15][16][17][18][19] ACEIs (Group A and C) had a neutral effect on renal function and SUA levels ( Table 2). These differences in renal function may have influenced the RRRs.…”
Section: Discussionmentioning
confidence: 99%
“…6,36,[38][39][40]53,128 It is also relevant that recent trials have shown that aggressive treatment with statins improves serum creatinine and urate levels. [129][130][131][132][133][134][135][136][137] These findings probably reflect an improved creatinine clearance. In turn, this effect is probably another consequence of improved blood flow following treatment with statins.…”
mentioning
confidence: 99%